Wacana KB Krama Bali : Analisis Persepsi Warganet di Media Sosial Facebook - I Made Sarmita (Pusat Kajian Bali Universitas Udayana, 2019)
This study aims to determine the netizen perceptions related to Balinese family planning (KB Krama Bali) discourse on Facebook. Unlike general principle of family planning in Indonesia which limit family to have two children, in Bali the allowing number is four. To achieve the study objective, the method used is qualitative. The study show that: 1) There are variations in the coverage of the KB Krama Bali discourse on Facebook by several online media, seen from the title and intensity of the news. The variety of news coverage is inseparable from the internal policies and external influences of the media; 2) Most of the attitude of netizens towards the KB Krama Bali discourse is agree (47%). This shows that some of the netizens were enthusiastic about the existence of the KB Krama Bali, indicating that Balinese cultural values ??have a more important role than other values ??related to child ownership; 3) Netizens expectations of the KB Krama Bali discourse vary, but only 3 things stand out, namely no further expectations, incentives, and priorities in other programs. From this expectation, it is identified that economic and cultural values ??have a vital role in children's values. Keywords: KB krama Bali, perception, social media, facebook